Mutual Integration Of Disciplines In Education Of Students For The Engineering Profession - Shomirzaev Makhmatmurod Khuramovich; Mengnorov Javohir Jasur o'g'li (Genius Publishing Group, 2024)
This article is covered by the fact that in the educational process, students are able to master the disciplines necessary for the acquisition of knowledge, skills and qualifications necessary for the implementation of professional activities and apply them at a high level in practice
Keywords: student; studentupbringing; engineer